Protein-Inorganic Hybrid Nanoflowers as Efficient Biomimetic Antibiotics in the Treatment of Bacterial Infection - Zhou, Ying; Li, Ying; Fei, Yunwei; Zhang, Mingrui; Wang, Shuang; Li, Fuqiu; Bao, Xingfu (Frontiers in Chemistry, 2021)
Nanozymes have been developed as new generation of biomimetic antibiotics against wound infection. However, most of new-developed nanozymes based on inorganic particles or hybrid ones usually originate from incompatible raw materials or unwanted metal salts, highly limiting their further biomedical usages. To overcome above drawbacks, it is highly required to develop novel nanozymes with great antibacterial activity by using biocompatible reagents and endogenous metal species as raw materials. Here, we demonstrated that bovine serum albumin enwrapped copper phosphate-based protein-inorganic hybrid nanoflowers possessed intrinsic peroxidase-like activity, which could be used as efficient biomimetic antibiotics against bacterial infection via the nanozyme-mediated generation of high toxic reactive oxygen species (ROS). With the admirable peroxidase-like activity, our nanoflowers could efficiently kill drug-resistance bacteria under physiological conditions, improve the wound healing after pathogen-induced infection, as well as avoid the potential tissue injury in time. Comprehensive toxicity exploration of these nanoflowers indicated their high biocompatibility and excellent biosafety. Our current strategy towards the design of protein-inorganic hybrid nanozymes with high biosafety and few side effects could provide a new paradigm for the development of nanozyme-based antibacterial platform in future.